Geographic Information System for Booking Beauty Salon and Barber Shop with an Android-Based ECRM Approach - Dharma Krisna Putra, Kadek; Piarsa, I Nyoman; Sukarsa, I Made (Scientific Journal of Informatics, 2020)
Beauty salons and barber shop are a necessity for almost everyone. Nowadays, the business processes of them mostly still use conventional methods. The method gives obstacles to customers who have a lot of activities, for example, they have to come directly to the beauty salon or barber shop to take the queue. In addition, it is hard to promote, communicate and assess without E-CRM media. The location is also difficult to find because there is no guide mark on Google Maps. The Geographic Information System for Booking Beauty Salon and Barber Shop provides solutions for making scheduled bookings and transactions by using the e-CRM approach as in the application of promotional features to attract customers. There are some features offered in the application, such as chat features for communication, rating and review features to assess the services obtained, and route feature as a solution to show the location of selected vendors. The implementation process requires an Android smartphone and a computer device with software including Android Studio, SQLYog, XAMPP, and Visual Studio Code. The results of the implementation of the system based on the questionnaire showed 25.8% answered 'excellent', 45.7% answered 'good', 28.3% answered 'enough', and 0.2% answered 'bad'.